The Impact Of Reading English Newspapers For Improving Vocabulary Mastery And Reading Skills (A Study Based On Grade 08 Students Of Mahmud Ladies College, Kalmunai) - MR. Rukshana Begum; MR. Rishad Muhammed; S.Umashankar; MB. Nowzath (Amandemen: Journal of Learning, Teaching and Educational Studies, 2025)
This research aims to explore the effect of reading English newspapers on enhancing reading skills and vocabulary knowledge among students at Mahmud Ladies College, Kalmunai. The study follows an experimental design, targeting grade 8 students from MLCK. Participants were divided into two groups of 30 students each. Data was gathered using tests and questionnaires. Students were given pre-test to know their ability. After conducting treatment to the experimental group, the researcher conducted post-test for both groups to know the students’ progress before and after treatment. Drawing from the results of tests and questionnaires, the research investigates the influence of English-language newspapers on the improvement of vocabulary acquisition and reading proficiency. The results showed a statistically significant improvement, suggesting that students’ language skills improved over time through this method.